DO NOT JUDGE THESE POTATOES BY IT PEEL:: Urban Consumers’ Perceptions of Imperfect Produce - Whisnu Febry Afrianto; Budiyoko Budiyoko (Universitas Perjuangan Tasikmalaya, 2022)
Even though these products have the same nutritional content, imperfect vegetable and fruit products are often ignored and discarded by consumers. This condition has resulted in an increasing problem of food loss and food waste, from the producer to the consumer level. This paper aimed to investigate consumer perceptions of imperfect vegetable products. The research design used two approaches, such as (1) hedonic test experiments and (2) group discussion forums (FGD). The participants were urban people who were living in Jakarta. Participants assessed the level of preference (hedonic) on color, aroma, texture, and taste. Potatoes used in this study were (Sample 1) potatoes grade A and (Sample 2) potatoes grade B. Potatoes sample 1 has a good shape, size, and only a minor blemish level. In contrast, potatoes sample 2 has a smaller size, not good condition, and blemish level. Investigation through the Mann-Whitney test showed that all parameters were not significantly different (p<0.05) for all variables. This indicated that consumers could accept imperfect produce. However, in terms of consumer behavior, cosmetics and appearance products are considered in choosing potatoes.